Cannabidiol in Pharmacoresistant Epilepsy: Clinical Pharmacokinetic Data From an Expanded Access Program - Contin, Manuela; Mohamed, Susan; Santucci, Margherita; Lodi, Monica Anna Maria; Russo, Emilio; Mecarelli, Oriano; CBD LICE Italy Study Group, (Frontiers in Pharmacology, 2021)
Background and Aim: Data on the clinical pharmacokinetics of cannabidiol (CBD) are scanty. We explored the effect of demographic and clinical variables on plasma concentrations of purified CBD in patients with Dravet (DS) and Lennox-Gastaut (LGS) syndrome. Methods: The study design was open, prospective, multicenter expanded access program. Venous blood samples were drawn from patients between 8-9 am, before the CBD morning dose, 12-hour apart from the last evening dose and then 2.5 hours after their usual morning dose. Results: We collected 127 plasma samples (67-morning pre-dosing and 60 post-dosing) from 43 patients (24 females, 19 males), 27 with LGS and 16 with DS. Mean ± standard deviation age was 26±15 years. Duration of CBD treatment averaged 4.2±2.9 months at 13.2±4.6 mg/kg/day. CBD median trough plasma concentration was 91 ng/mL; it doubled to 190 ng/mL 2.5 hours post-dosing (p<0.001). Cannabidiol trough plasma concentrations were linearly related to daily doses (r= 0.564, p<0.001). Median trough CBD plasma concentration-to-weight-adjusted dose ratio (C/D) was 32% higher (p<0.02) in plasma samples from subjects aged 18 and over than in under 18. Sex and concomitant ASMs were not associated with significant variations in CBD C/D, but caution is required due to the potential influence of confounders. Conclusion: These are the first data on CBD pharmacokinetics in children and adults with LGS or DS in a real-world setting. The most relevant finding was the higher CBD C/D in adults. In practice, reduced weight-normalized doses might be required with ageing to achieve the same CBD plasma levels.